Sustainable Investments and ESG factors - Camillo Giliberto (Risk Management Magazine, 2024)
In recent years the transition towards a model of sustainable economic development has assumed central importance for the financial system. The inclusion of environmental, social and governance aspects (ESG – Environmental, Social and Governance) is taking an important role in the investment and issuance process, encouraging innovation and the growth of sustainable finance, which sees the application of the concept of sustainable development to financial activities. The energy crisis and the Russia-Ukraine war are two factors that can contribute to accelerating the energy transition to reduce dependence on Russian gas imports and more generally on fossil fuels. The war resulted in rising energy prices, further pushing European countries to reduce their dependence on Russian oil and gas supplies. Regulators are increasingly focused on transparency regarding sustainable investments. Financing the transition to a low-carbon economy is crucial today, given the impact that climate change continues to have on economies, businesses and communities globally. To finance decarbonisation across sectors, innovative solutions will be needed, the development of which will require large amounts of capital. In this context, the sustainable bond market has become of considerable importance to find the financial resources necessary to fill a financial gap of 4,100 billion dollars by 2050.